THE INFLUENCE OF BRAND AMBASSADORS AND ADVERTISING ON LAZADA PURCHASE DECISIONS - Gugyh Susandy; Tina Rahayu (STIESA Press, 2025)
Marketing management is the process of planning strategies to determine target markets and ensure customer satisfaction through elements of product, distribution, promotion, and pricing. In promotion, companies use methods such as advertising, sales promotions, public relations, and personal selling to attract consumer attention and build long-term relationships. Consumer behavior includes how they search for, purchase, use, and evaluate products to fulfill their needs. The purchase decision process involves need recognition, information search, alternative evaluation, and the final decision. A brand ambassador plays a crucial role in enhancing brand image and driving sales through their popularity and credibility. Effective advertising should convey the product's benefits, have distinctive features, and provide trustworthy information. This study analyzes the influence of Brand Ambassador and Advertising on the Purchase Decisions of Lazada users in Subang Regency. The method used is quantitative with a descriptive-verificative type of research, aimed at describing and testing the relationships between variables through an explanatory survey. Primary data were collected from 100 respondents through an online questionnaire, while secondary data were obtained from literature. The analysis was conducted using SPSS software to test the validity and reliability of the research instruments, resulting in findings that verify the hypotheses. Based on the validity test, all variables—Brand Ambassador (X1), Advertising (X2), and Purchase Decision (Y)—met the criteria at a 5% significance level. The t-test showed that for the X1 variable, the calculated t-value was 3.028 (t-table 1.984, significance 0.003), meaning that Brand Ambassador influences Purchase Decision, thus H1 is accepted. For the X2 variable, the calculated t-value was 9.406 (t-table 1.984, significance 0.000), indicating that Advertising also influences Purchase Decision, thus H2 is accepted. The F-test showed a calculated F-value of 22.03 (F-table 3.09, significance 0.000), meaning that Brand Ambassador and Advertising simultaneously influence Purchase Decision, thus H3 is accepted.